Nurses Perception of Practical Environment Relationship with Patient Satisfaction in Government Hospital Lahore - Hameed, Sobia; Hussain, M. (International Journal of Social Sciences and Management, 2019)
Introduction: The practical environment is described as the surrounding environments in which an employee works. Nurses practical environment control the delivery of nursing care. It is also important for nurses to develop a awareness about their own perception about working environment that have a positive impact on their performance and enhance the patients’ satisfaction. Objective: The objective of the study is to evaluate Nurses perception of practical environment relationship with patient satisfaction in Government Hospital Lahore. Methodology: Descriptive correlational study design used for study. Sample size Sixty nurses (n=60) and one thirty-three patients (n=133) were selected for study. The tool used for this study included a demographic data, Practice Environment scale Nurse Work Index (PES-NWI) developed by Dr. Eileen Lake (2002), and 2nd tool for patient satisfaction the Hospital Consumer Assessment of Healthcare Provides and Systems (HCAHPS) survey for patients developed by (Long, 2012) used for the study. Results: The results of the study showed the significance positive correlation between the nurse perception and patients’ satisfaction about practical environment. Conclusion: This study concludes that the nurse's perception about nurse practical environment and patient satisfaction from hospital environment show positive relationship. The perception of nurses and patients significantly correlated with practical environment. Healthy environment positive effect on patient satisfaction. Good nursing care enhance patient satisfaction by hospital environment and they will cure early. Int. J. Soc. Sc. Manage. Vol. 6, Issue-3: 75-81